Fabrication and Characterization of Chitosan-Polyethylene Glycol (Ch-Peg) Based Hydrogels and Evaluation of Their Potency in Rat Skin Wound Model - Md Mahmudul Hasan; Md Forhad Uddin; Nayera Zabin; Md Salman Shakil; Morshed Alam; Fahima Jahan Achal; Most. Hosney Ara Begum; Md Sakib Hossen; Md Ashraful Hasan; Md Mahbubul Morshed (International Journal of Biomaterials)
Thermal burns are a major cause of death and suffering around the globe. They can cause debilitating, life-altering injuries as well as lead to significant psychological and financial consequences. Several research works have been conducted in attempt to find a wound healing therapy that is successful. At present, hydrogels have been widely used in cutting-edge research for this purpose because they have suitable properties. This study aimed to see how therapy with chitosan-polyethylene glycol (Ch-Peg) based hydrogels affected the healing of burn wounds in rats. With the concern of public health, xanthan gum (X), boric acid (B), gelatin (Ge), polyethylene glycol (Peg), chitosan (Ch), glutaraldehyde (G), and HPLC-grade water were prepared using X : Ge : G, X : Ge : Peg : G, X : Ge : Ch : G, X : Ge : Peg : Ch : G, X : Ge : B : Ch : G, X : Ge : B : Peg : G, and X : Ge : B : Peg : Ch : G. The produced composite hydrogels were examined for swelling ability, biodegradability, rheological characteristics, and porosity. The 3D structure of the hydrogel was revealed by scanning electron microscopy (SEM). After that, the structural characterization technique named Fourier-transform infrared spectroscopy (FTIR) was used to describe the composites (SEM). Lastly, in a rat skin wound model, the efficacy of the produced hydrogels was studied. Swelling ability, biodegradability, rheological properties, and porosity were all demonstrated in composite hydrogels that contained over 90% water. Hydrogels with good polymeric networks and porosity were observed using SEM. The existence of bound water and free, intra- and intermolecule hydrogen-linked OH and NH in the hydrogels was confirmed using FTIR. In a secondary burned rat model, all hydrogels showed significant wound healing effectiveness when compared to controls. When compared to other composite hydrogels, wounds treated with X : Ge : Peg : Ch : G, X : Ge : B : Peg : G, and X : Ge : B : Peg : Ch:G recovered faster after 28 days. In conclusion, this research suggests that X : Ge : Peg : Ch : G, X : Ge : B : Peg : G, and X : Ge : B : Peg : Ch : G could be used to treat skin injuries in the clinic.